The Core-Cusp Problem - W. J. G. de Blok (Advances in Astronomy)
This paper gives an overview of the attempts to determine the distribution of dark matter in low surface brightness disk and gas-rich dwarf galaxies, both through observations and computer simulations. Observations seem to indicate an approximately constant dark matter density in the inner parts of galaxies, while cosmological computer simulations indicate a steep power-law-like behaviour. This difference has become known as the “core/cusp problem,” and it remains one of the unsolved problems in small-scale cosmology.